Preliminary development and evaluation of an appearance-based dissonance induction intervention for reducing UV exposure. (January 2015) - Chait, Sari R.; Thompson, J. Kevin; Jacobsen, Paul B.
Highlights: Dissonance induction evaluated as treatment for tanning and sunscreen related behaviors. Dissonance approach reduced tanning when compared to the healthy lifestyle control condition. Psychoeducation procedures did not differ from healthy lifestyle strategies on any variable. Supports future research evaluating appearance-based tanning interventions. Abstract: The current study examined the feasibility of an appearance-based dissonance induction approach for the modification of tanning and sunscreen use behaviors. Undergraduate female students were randomized to: a healthy lifestyle condition, an appearance-based dissonance condition, or an appearance-based psychoeducation condition. Reports of tanning and sunscreen use were collected immediately before and 1 month following intervention ( N = 225). Relative to the healthy lifestyle condition, participants in the dissonance condition reported a significant reduction in daily hours spent tanning. Additionally, sunscreen use on the body decreased significantly for the healthy lifestyle group, but did not change for the dissonance group. The psychoeducation condition did not differ from the healthy lifestyle condition on any measure. These findings should encourage additional research into the use of dissonance induction as an appearance-based strategy for promoting reductions in UV exposure.